Ventricular Remodeling Induced by Tissue Vitamin A Deficiency in Rats - Gaiolla, Paula Schmidt Azevedo [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Justulin, Luis A. [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Novelli, Ethel [UNESP]; Seiva, Fabio [UNESP]; Ebaid, Geovana Xavier [UNESP]; Campana, Alvaro O. [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP] (Karger, 2010)
Background/Aims: Experimental studies suggest that vitamin A plays a role in regulating cardiac structure and function. We tested the hypothesis that cardiac vitamin A deficiency is associated with adverse myocardial remodeling in young adult rats. Methods: Two groups of young female rats, control (C - n = 29) and tissue vitamin A deficient (RVA - n = 31), were subjected to transthoracic echocardiography exam, isolated rat heart study and biochemical study. Results: The RVA rats showed a reduced total vitamin A concentration in both the liver and heart [vitamin A in heart, mu mol/kg (C = 0.95 +/- 0.44 and RVA = 0.24 +/- 0.16, p = 0.01)] with the same serum retinol levels (C = 0.73 +/- 0.29 mu mol/L e RVA = 0.62 +/- 0.17 mu mol/L, p = 0.34). The RVA rats showed higher left ventricular diameters and reduced systolic function. The RVA rats also demonstrated increased lipid hydroperoxide/total antioxidant capacity ratio and cardiac levels of IFN-gamma and TNF-alpha but not of metalloproteinase (MMP)-2 and -9 activity. on the other hand, the RVA rats had decreased levels of beta-hydroxyacylcoenzyme A dehydrogenase and lactate dehydrogenase. Conclusions: Tissue vitamin A deficiency stimulated cardiac remodeling and ventricular dysfunction. Additionally, the data support the involvement of oxidative stress, energy metabolism, and cytokine production in this remodeling process. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Inflammation; Oxidative stress; Energetic metabolism; Vitamin A; Remodeling